Directors' duties in Singapore: Law and perceptions - KOH, Pearlie M. C. (Institutional Knowledge at Singapore Management University, 2019)
It is trite that the law on directors' duties is an important part of corporate governance. It is therefore unsurprising that a large part of extant research in the area is focused on understanding what the law requires, and how it applies or should apply in any particular situation. Such research is however largely reactive. In our research, we set out to look at duties from the perspective of the directors, with a view to appreciating how Singapore directors understand the law as it applies to them. The impetus for this is three-fold: First, to assess the depth of awareness amongst directors of the law on directors' duties; second, to ascertain if there is any divergence between the law's conceptualization of what is in the company's interests, and the director's own view as to how he or she would act in fact; and third, and flowing from the preceding, to assess the need for providing or improving knowledge enhancement courses targeted specifically at company directors. To collect the necessary data, we reached out to registered company directors of both listed companies and private companies to complete a survey. We released the survey online, and also conducted face-to-face interviews. Our article presents and analyzes the results of the survey. © 2019 National University of Singapore.